TOTO, positioning plumbing products globally - Baack, Daniel W.; Harris, Eric G.; Baack, Donald ([London] : SAGE, 2016)
TOTO is the world's largest manufacturer of toilets. It holds its position based on beliefs about company innovations combined with an emphasis on sustainability. This case discusses the firm's international marketing practices and the ethical guidelines that it follows.
Originally Published in: Baack, D. W., Harris, E. G., & Baack, D. (2012). TOTO: Positioning Plumbing Products Globally. In International marketing (pp. 187-188). Los Angeles: SAGE Publications, Inc. ISBN: 9781452226354.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Export marketing -- Case studies; Plumbing equipment industry -- Case studies